2021
DOI: 10.1093/inthealth/ihab005
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immunological kinetics of severe acute respiratory syndrome coronavirus 2 infection and diagnostic performance of serological assays for coronavirus disease 2019: an analysis of global reports

Abstract: As the coronavirus disease 2019 (COVID-19) pandemic continues to rise and second waves are reported in some countries, serological test kits and strips are being considered to scale up an adequate laboratory response. This study provides an update on the kinetics of humoral immune response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and performance characteristics of serological protocols (lateral flow assay [LFA], chemiluminescence immunoassay [CLIA] and ELISA) used for evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…Espi et al [ 21 ] screened 106 HDPs 10–14 days after the second dose of BNT162b2 vaccine and registered 19 non-responders (18%), in contrast to the control group in which 100% seroconversion was detected. In accordance with the above results, Strengert et al [ 23 ] and Stumpf et al [ 34 ] detected diminished antibody levels in patients undergoing HD, which, however, reached higher rates of positive immune responses of up to 95%. Of great interest were the findings of Schrezenmeier et al [ 22 ] who observed a gradual increase in the proportion of cases reactive for SARS-CoV-2-IgG antibodies between 1- and 3-week samples, which finally seemed to decrease at a 10-month follow up.…”
Section: Vaccine-elicited Humoral Immune Response Among Dialysis Pati...supporting
confidence: 74%
See 1 more Smart Citation
“…Espi et al [ 21 ] screened 106 HDPs 10–14 days after the second dose of BNT162b2 vaccine and registered 19 non-responders (18%), in contrast to the control group in which 100% seroconversion was detected. In accordance with the above results, Strengert et al [ 23 ] and Stumpf et al [ 34 ] detected diminished antibody levels in patients undergoing HD, which, however, reached higher rates of positive immune responses of up to 95%. Of great interest were the findings of Schrezenmeier et al [ 22 ] who observed a gradual increase in the proportion of cases reactive for SARS-CoV-2-IgG antibodies between 1- and 3-week samples, which finally seemed to decrease at a 10-month follow up.…”
Section: Vaccine-elicited Humoral Immune Response Among Dialysis Pati...supporting
confidence: 74%
“…The adequate laboratory examination of humoral response levels plays a highly significant role in assessing vaccination efficacy. Serological protocols relying on the quantification of specific anti-viral antibodies are considered as reliable biomarkers [ 34 ]. As immunoglobulins targeting receptor binding domain (RBD) account for up to 90% of the formed anti-SARS-CoV-2-specific antibodies [ 35 ], all analyzed studies aim to measure IgG or IgA titers against the S1 domain.…”
Section: Vaccine-elicited Humoral Immune Response Among Dialysis Pati...mentioning
confidence: 99%
“…Anti-SARS-CoV-2 IgM is not detected in individuals who have not been infected with SARS-CoV-2 and is also absent in the early stage of infection. After exposure to SARS-CoV-2 infection, IgM values increase, peaking in the third week [105] . The detection sensitivity is significantly higher than that of RT-qPCR 1 week after the disease onset.…”
Section: Methods To Detect Virus Aerosolsmentioning
confidence: 99%
“…Likewise, the differences between SARS-CoV and SARS-CoV-2 RBD are sufficiently important that there is no cross binding of specific monoclonal antibodies (Wrapp et al, 2020). Consequently, it is pertinent to define S protein, particularly the RBD, in SARS-CoV-2 as both a therapeutic and diagnostic target (Shi et al, 2020;Tai et al, 2020;Wrapp et al, 2020;Zhao et al, 2020;Emeribe et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In COVID-19, the cumulative seroconversion rate increases rapidly during the first 2 weeks of the onset of SARS-CoV-2 infection, exceeding 50% (Zhao et al, 2020). The adaptive response begins during the ongoing infection (between 1 week and 2 weeks), with the increase of IgM levels until reaching a maximum (in 3 weeks) and then decreasing in an inverse relationship with the concomitant increase of IgG levels (3 weeks-7 weeks), whose affinity for the antigen and neutralization capacity is greater (Galipeau et al, 2020;Guo et al , 2020;Post et al, 2020;Sette and Crotty, 2021;Emeribe et al, 2022).…”
Section: Introductionmentioning
confidence: 99%